Chronic effects of temperature and nitrate pollution on Daphnia magna: Is this cladoceran suitable for widespread use as a tertiary treatment?. (15th October 2015) - Maceda-Veiga, Alberto; Webster, Gordon; Canals, Oriol; Salvadó, Humbert; Weightman, Andrew J.; Cable, Jo
Abstract: Effluent clarification and disinfection are major challenges in wastewater management. The cladoceran Daphnia magna has been proposed as a cost-effective and ecosystem-friendly option to clarify and disinfect secondary effluents, but its efficacy has not been fully tested under different sewage conditions. The present study explores the effects of temperature and nitrate on the efficacy of D. magna as a tertiary treatment at two different scales (individual assays and microcosms). Individual assays were employed to determine direct effects of temperature and/or nitrate on D. magna cultured in a suspension of organic matter. Using microcosms under the same environmental conditions, we explored the clearing efficacy of D. magna interacting with a natural microbial community. Individual assays revealed that D. magna mortality increased by 17% at 26 °C, 21% at >250 mg NO3 − /l and by 60% at 26 °C and at >250 mg NO3 − /l, and individuals displayed reduced body size, filtering rates and fecundity when compared to those at 21 °C and <40 mg NO3 − /l. Improved performance under these conditions was also mirrored in the microcosms, with a higher density of D. magna (>100 ind/l) at 21 °C and <40 mg NO3 − /l compared to the number (0–21 ind/l) at 26 °C and/or >250 mg NO3 − /l. In the microcosms at 21 °C and <40 mg NO3 − /l, turbidity and the density of bacteria, protists and micro-metazoa decreased in relation to those at 26 °C and/or >250 mg NO3 − /l. Each treatment developed a unique and characteristic microbial assemblage, and D. magna was identified as the major driver of the community structure of protists and micro-metazoa. This enabled us to determine taxa vulnerability to D. magna grazing, and to re-define their tolerance thresholds for nitrate. In conclusion, this study increases our knowledge of how microbes respond to temperature and nitrate pollution, and highlights that D. magna efficacy as a tertiary treatment can be seriously compromised by variable environmental conditions. Graphical abstract: The efficacy of Daphnia magna as a tertiary treatment can be compromised under elevated temperature and/or nitrate levels. Highlights: Daphnia magna as a cost-effective option in the sewage treatment process. D. magna clarifies water and reduces microbial load at 21 °C and <40 mg nitrate/l. D. magna efficacy was seriously compromised at 26 °C and >250 mg nitrate/l. Reducing bacterial load is likely to be challenging using filter-feeders. Microbes response to warming, nitrate pollution and D. magna grazing.